Level of Knowledge and Hygiene Practices of Food Handlers and Escherichia Coli Contamination of Food in “B” Catering - Nurhasanah, Siti Fadilla; Suhelmi, Reni; Isworo, Yanie (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
A food handler is a person who performs food processing activities, ranging from raw materials to food served. Knowledge of food hygiene and the attitude of food stewards will certainly influence sanitary hygiene practices, especially when processing food, resulting in foods not contaminated by physical, chemical, or biological substances. The study aimed to determine the level of knowledge and hygiene practices among food stewards and the presence of Escherichia coli in the food at “B” Catering in Samarinda City. The research method was quantitative with a descriptive approach, a total sampling technique for food handler samples, and then, for food samples, the menu of interest was selected. Results The knowledge level of food stewards was 83.3%, comparable to 13.3%, while less than 3.3% possessed this level of knowledge. Food inspectors who practiced good hygiene accounted for 66.7%, those who practiced sufficient hygiene accounted for 30.0%, and those who practiced less hygiene accounted for 3.3%. Additionally, laboratory tests revealed that food samples in the excellent quality category, with a 0 CFU/gr value, were not contaminated with Escherichia coli. The conclusion of the knowledge level overview, the hygiene practices of food handlers, and the contamination of food by Escherichia coli all yielded positive results.